Assessment of Livestock Service Delivery Pattern by Mobile Veterinary Units (Mvus) in Kandhamal District of Odisha - Jena, Anupama; Chander, Mahesh (Indian Journal of Veterinary Sciences and Biotechnology, 2017)
An ex-post-facto study was conducted to assess the livestock service delivery pattern of Mobile Veterinary Unit (MVU), with a sample size of 90 farmers, who had availed the services of MVU, in Kandhamal district of Odisha. According to Total weighed mean square analysis (TWMS), preventive services were ranked first as the most available services in MVU, while in other veterinary service centers, curative services were most available. Further, cent percent respondents reported that the services by MVU were supply driven, whereas, in case of other agencies, only 16.7 per cent told that it was supply driven. Majority (76.7%) of respondents said MVU provides service on demand, moreover, cent percent respondents reported ‘doorstep’ availability of MVU services. Majority (57.8%) of farmers received services through MVUs three times in last 12 months, while, only two times by any other veterinary service centers during the same period. The minimum fee charged for the services delivered through MVU was only Rs. 2.0, while, Rs. 50-100 were being charged by other veterinary service centers.
Keywords: Livestock service delivery pattern; MVU; Kandhamal; TWMS